Effect of Follicular Proteins on Buffalo Sperm Functions during Cryopreservation - KUMARESAN, A; ANSARI, M R; GARG, ABHISHEK (The Indian Journal of Animal Reproduction, 2023)
A study was undertaken to assess the effect of follicular proteins on freezability of buffalospermatozoa. Follicular fluid was aspirated from the follicles (>5mm) of buffalo ovaries obtained fromslaughterhouse. The follicular fluid was centrifuged (3000 rpm; 30 minutes), filtered (0.2μ) and frozen at -20°C. The proteins in pooled follicular fluids were precipitated over night t. sing ammonium sulphate,centrifuged ( I 0000 rpm; 30 minutes) and dialyzed (> I 0kDa). After protein estim:1tion, aliquots of samplescontaining IO mg proteins were lyophilized in cryovials and stored frozen at -20°( ')ix pooled good qualityejaculates from two Murrah buffalo bulls were used as split ejaculates. After r 1 semen analysis, eachpooled ejaculate was splited into five parts and extended in Tris-Egg yolk-Citrate l ·.tr 1 er (2( '~ egg )Olk:7% glycerol), so that final diiution yielded approximately 60 million sperm per ml and . -yopres, rved in 0.5ml French straws (30 million sperm cells/straw) in LN2 (-I 96°C). Prior to freezing, one pa1i of eaL,1 ejaculatewas added with follicular proteins at the rate of lmg/ml of extended semen while another patt w, , frozewithout any added proteins (control). Semen samples (pre-freeze· and frozen-thawed) were evaluated fo.motility, viability and intact acrosome percentages, sperm penetration distance in cervical mucus (BCMPT)and swollen sperm percentage in response to hypo-osmotic solution (HOSST). Besides this, frozen thawedsperms were washed and incubated in spe,m-T ALP at 37°c for 6 hrs. The sperm motility, viability and. intactacrosome percentages were evaluated at hourly interval. Addition of follicular proteins maintainedsignificantly (P
Keywords: Buffalo; Follicular proteins; Cryopreservation; Spermatozoa